STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN MUTU KELULUSAN SANTRI/SISWA MA'HAD PESANTREN MUSTHAFAWIAH PURBA BARU - Imam Amir Musthofa; Muhammad Rifa’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies implemented by the head of madrasah in improving the quality of student graduation at Ma'had Pesantren Musthafawiyah Purba Baru. This research uses a qualitative approach with a case study method. The independent variable in this study is the strategy of the head of madrasah (X), which consists of five dimensions: curriculum development (X1), teacher quality improvement (X2), technology integration (X3), character education (X4), and partnership with parents (X5). The dependent variable is the quality of student graduation (Y), measured through academic achievement, discipline, spiritual values, and social competence. Data collection techniques include observation, in-depth interviews, and documentation. The results show that the strategy of the head of madrasah has a significant effect on improving the quality of graduation. The most dominant dimension is teacher quality improvement (X2) with a percentage of 85%, followed by character education (X4) at 80%, curriculum development (X1) at 78%, partnership with parents (X5) at 75%, and technology integration (X3) at 72%. Supporting factors include commitment from all parties, adequate facilities, and conducive learning environment. Inhibiting factors include limited funding and varying teacher competencies.